Using the Indigenous Knowledge of Jatropha - The Use of Jatropha Curcas Oil as Raw Material and Fuel - World Bank (Washington, DC, 2012)
Jatropha curcas is a plant of Latin American origin, now widespread through arid, and semiarid tropical regions of the world. It is a drought-resistant perennial, that grows on marginal soils, and, as a close relative to the castor plant, its oil has the same medical properties. In Mali, it is well-known and has long been recognized as a plant of many uses: Jatropha hedges not only protect gardens from hungry livestock, but reduces damage, and erosion from wind, and water. As of the 1930s, the oil potential as a fuel source was also recognized, currently used to substitute for the "gazoil" mixture used in the Indian type diesel engines, that drive grain mills, and water pumps in rural areas of Mali, while its high-quality oil extracted by engine-driven expellers, or by the sediment of the oil purification process, may be used for larger-scale soap making in rural areas, providing local women the chance to gain additional income, thus strengthening their economic position. The note examines all these possibilities, as well as the potential further uses of Jatropha oil as a renewable energy source, being currently researched. To summarize, Jatropha is characterized by the many positive ecological, energetic, and economic aspects which are attached with its commercial exploitation, which may well improve the environment, and food production.